Influence of Lipid Class Used for Omega-3 Fatty Acid Supplementation on Liver Fat Accumulation in MASLD - Sabinari, I; Horakova, O; Cajka, T; Kleinova, V; Wieckowski, MR; Rossmeisl, M (Physiological research, 2024)
Metabolic dysfunction-associated steatotic liver disease (MASLD) occurs in subjects with obesity and metabolic syndrome. MASLD may progress from simple steatosis (i.e., hepatic steatosis) to steatohepatitis, characterized by inflammatory changes and liver cell damage, substantially increasing mortality. Lifestyle measures associated with weight loss and/or appropriate diet help reduce liver fat accumulation, thereby potentially limiting progression to steatohepatitis. As for diet, both total energy and macronutrient composition significantly influence the liver’s fat content. For example, the type of dietary fatty acids can affect the metabolism of lipids and hence their tissue accumulation, with saturated fatty acids having a greater ability to promote fat storage in the liver than polyunsaturated ones. In particular, polyunsaturated fatty acids of n-3 series (omega-3), such as docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), have been intensively studied for their antisteatotic effects, both in preclinical animal models of obesity and hepatic steatosis and in overweight/obese patients. Their effects may depend not only on the dose and duration of administration of omega-3, or DHA/EPA ratio, but also on the lipid class used for their supplementation. This review summarizes the available evidence from recent comparative studies using omega-3 supplementation via different lipid classes. Albeit the evidence is mainly limited to preclinical studies, it suggests that phospholipids and possibly wax esters could provide greater efficacy against MASLD compared to traditional chemical forms of omega-3 supplementation (i.e., triacylglycerols, ethyl esters). This cannot be attributed solely to improved EPA and/or DHA bioavailability, but other mechanisms may be involved.